Controlling ultracold p -wave collisions with nonresonant light: Predictions of an asymptotic model - Crubellier, Anne; Gonzalez-Ferez, Rosario; Koch, Christiane P.; Luc-Koenig, Eliane (Physical Review A, 2019)
Interactions in a spin-polarized ultracold Fermi gas are governed by p-wave collisions and can be characterized by the p-wave scattering volume. Control of these collisions by Feshbach resonances is hampered by huge inelastic losses. Here, we suggest nonresonant light control of p-wave collisions, exploiting the anisotropic coupling of nonresonant light to the polarizability of the atoms. The p-wave scattering volume can be controlled by strong nonresonant light, in close analogy to the s-wave scattering length. For collision partners that are tightly trapped, the nonresonant light induces an energy shift directly related to the scattering volume (as defined by A. Crubellier, R. González-Férez, C. P. Koch, and E. Luc-Koenig, preceding paper, Phys. Rev. A 99, 032709 (2019)10.1103/PhysRevA.99.032709. This effect could be used to climb the ladder of the trap. We also show that controlling the scattering volume implies control, at least roughly, over the orientation at short interatomic distances of the interparticle axis relative to the polarization direction of the light. Our proposal is based on an asymptotic model that explicitly accounts for the anisotropic dipole-dipole interaction which governs the ultracold collision dynamics at long range.
CRIS-Team Scopus Importer:2023-04-20